Assessment of Tools for Marker-Assisted Selection in a Marine Commercial Species: Significant Association between MSTN-1 Gene Polymorphism and Growth Traits - Irma Sánchez-Ramos; Ismael Cross; Jaroslav Mácha; Gonzalo Martínez-Rodríguez; Vladimir Krylov; Laureana Rebordinos (The Scientific World Journal)
Growth is a priority trait from the point of view of genetic improvement. Molecular markers linked to quantitative trait loci (QTL) have been regarded as useful for marker-assisted selection in complex traits as growth. Polymorphisms have been studied in five candidate genes influencing growth in gilthead seabream (Sparus aurata): the growth hormone (GH), insulin-like growth factor-1 (IGF-1), myostatin (MSTN-1), prolactin (PRL), and somatolactin (SL) genes. Specimens evaluated were from a commercial broodstock comprising 131 breeders (from which 36 males and 44 females contributed to the progeny). In all samples eleven gene fragments, covering more than 13,000 bp, generated by PCR-RFLP, were analyzed; tests were made for significant associations between these markers and growth traits. ANOVA results showed a significant association between MSTN-1 gene polymorphism and growth traits. Pairwise tests revealed several RFLPs in the MSTN-1 gene with significant heterogeneity of genotypes among size groups. PRL and MSTN-1 genes presented linkage disequilibrium. The MSTN-1 gene was mapped in the centromeric region of a medium-size acrocentric chromosome pair.